Histological evaluation of goat's hair at different ages - Dal Monte, Maria Auxiliadora de B. L.; Costa, Roberto Germano; Grotta, Marinei; Bragagnoli, Gerson; Jacinto, Manuel Antônio Chagas; Medeiros, Ariosvaldo Nunes de (Brazilian Journal of Veterinary Research and Animal Science, 2005)
The objective of theis research was to analyze the skin of goats, identifying the structural differences in the cell level. It was used 16 animals, males, crossbred Alpine, using 4 animals in each slaughter, at the age of 180 days and older, used intervals of 45 days between each slaughter. After flaying the animals, it was removed samples of the skin from dorsal, palette, ventral, hind and lateral regions. These samples were placed in a Bouin solution an analyzed at cellular level, according to the paraffin inclusion routine. The 5 mm cuts were photomicrographed and analyzed. The goats skin that were 180 days old shown a thicker thermostatic layer of the skin, consequently with a greater density of follicles and glands. With age the reticular layer develops leading to the sheaves of fibers of the collagen.